2019
DOI: 10.24251/hicss.2019.278
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing Social Media For Lead Generation

Abstract: Social Media is the most prevalent platform for communication, forming and maintaining professional as well as social relationships. The growth of platforms and the exponential rise in the user base of social media websites like LinkedIn, Facebook and Twitter, is evidence of their widespread acceptance. They pose many opportunities for businesses to exploit this facet of digitally mediated relationships, for example spreading awareness about the business and engage with prospective customers. The focus of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Utilizing LinkedIn for lead generation involves leveraging social media platforms to establish and maintain professional relationships (Prakash et al, 2019). This aligns with the trend where social media, including LinkedIn, has become a primary platform for communication and relationship building in both professional and social contexts (Prakash et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 95%
See 1 more Smart Citation
“…Utilizing LinkedIn for lead generation involves leveraging social media platforms to establish and maintain professional relationships (Prakash et al, 2019). This aligns with the trend where social media, including LinkedIn, has become a primary platform for communication and relationship building in both professional and social contexts (Prakash et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 95%
“…Utilizing LinkedIn for lead generation involves leveraging social media platforms to establish and maintain professional relationships (Prakash et al, 2019). This aligns with the trend where social media, including LinkedIn, has become a primary platform for communication and relationship building in both professional and social contexts (Prakash et al, 2019). LinkedIn's structured and unstructured data provide valuable insights for lead generation and networking, making it a valuable tool for businesses seeking to attract and convert potential customers (Spilotro, 2023).…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, there is limited research available on this type of social media sales funnels for lead generation. Caton & Haas (2019) research on the subject has focused on a potential customer/employee point of view, introducing a methodology of seed profiles to better filter lead data. On the other hand, the research of Wilcox and Sussman (2014) has proven that SNPs have a significant impact on final conversion rates, even though their data is based on website conversions as the typical final stage.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several studies have also demonstrated the potential of OSN in defining people's sentiments about events, incidents, products, and services [41]. The potential of Twitter as a platform for improving awareness over variables of interest and thus supporting a more informed decision-making process has been highlighted in the literature for different areas, such as earthquake detection [46], influenza virus epidemics [1] [6], disasters [14] [25], elections [21], mobility [10], organizational issues [43], or crimes [33].…”
Section: Introductionmentioning
confidence: 99%